EVALUATION OF MULBERRY GERMPLASM BASED ON LEAF AND YIELD PARAMETERS - A. WANI, SHABIR; G. N. MALIK,; M. R. MIR,; G. PARVEEZ,; MAJID, NAINA; BHAT, M. ASHRAF (The Bioscan, 2014)
The nature and magnitude of genetic variability and their interrelationship were studied for leaf and yield traits in 17 genotypes of mulberry (Morus spp).Analysis of variance of Lamina length, Lamina width, Lamina weight, Petiole weight and Leaf petiole ratio by weight, Petiole length, Leaf petiole ratio by length and leaf yield per plant showed significant variation. Leaf yield was recorded highest (4.751 kg/plant) in Goshoerami followed by SKM33 (4.100 kg/plant) during spring season while as it was recorded (4.863 kg/plant) in Goshoerami and (4.450 kg/ plant) in SKM-33 during autumn season. The correlation coefficient showed significant association of leaf yield with lamina weight (0.72**); lamina length (0.37**) and petiole weight (0.60**). Divergence analysis grouped the genotypes into 3 clusters, cluster I contained 15 genotypes, cluster II and Cluster III contained 1 genotype each on pooled over spring. The genotypes were grouped in to 2 clusters, cluster I contained 16 genotypes and cluster II contained 1 genotype on pooled over autumn. The variability among the genotypes measured by inter-cluster distance showed variation, which can be utilised for mulberry crop improvement. Goshoerami and SKM-33 exhibit highest leaf yield which can utilized in future breeding programmes.